Insertion of Pyrenean farms in the lamb production chain in the region of Aragón - Maza M.T.; Manrique E.; Olaizola A. (Systèmes d'élevage et gestion de l'espace en montagnes et collines méditerranéennes, 1999)
This work analyses different aspects of the commercialisation of lambs on farms in the three most eastern Pyrenean valleys of the region of Aragón (Spain). Different components of the Aragonese lamb agro-food chain form the framework which has been used to gain an insight into the behaviour of Pyrenean farms. A prior analysis of the lamb flows, the dynamics of prices and the spatial location of the Refrigerated General Slaughterhouses is carried out at regional scale before looking in detail at the different ways in which lambs are commercialised by the farmers. In relation to the latter, the description given essentially covers the product commercialised, destinations in spatial terms, channels used, annual seasonality and the relationship with the production system used.